2015
DOI: 10.1055/s-0034-1398574
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aquatic Plyometric Training on Repeated Jumps, Drop Jumps and Muscle Damage

Abstract: The purpose of this study was to compare the effects of land- vs. aquatic based plyometric training programs on the drop jump, repeated jump performance and muscle damage. Sixty-five male students were randomly assigned to one of 3 groups: aquatic plyometric training group (APT), plyometric training group (PT) and control group (CG). Both experimental groups trained twice a week for 10 weeks performing the same number of sets and total jumps. The following variables were measured prior to, halfway through and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Lavanant et al [18] reported a significant increase in muscle power in the group undergoing aquatic training. Fabricius [17] observed that the group that trained in the land obtained significant development in the tests of speed, agility, and power of lower limbs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lavanant et al [18] reported a significant increase in muscle power in the group undergoing aquatic training. Fabricius [17] observed that the group that trained in the land obtained significant development in the tests of speed, agility, and power of lower limbs.…”
Section: Discussionmentioning
confidence: 96%
“…Buoyancy may proffer an upward thrust acting on any partially or fully immersed object in the direction opposite to gravity [17]. Aquatic PT (APT) has been indicated to reduce the symptoms of EIMD as compared with land PT (LPT) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, lower drop heights and less intense loads are preferable in the initial stages of adaptation to training and increases must be gradual 16 . Additionally, the load reduction during braking sub-phase in water can be one of the reasons for lower levels of delayed onset muscle soreness 23 and / or the lower concentration of muscular stress markers 9 reported in literature for individuals who perform aquatic plyometric training compared to those who perform ground plyometric training.…”
Section: Discussionmentioning
confidence: 99%
“…According to Flanagan and Comyns 16 and Walsh et al 18 , training using exercises in which SSC is slowly performed may not be as beneficial for athletes who primarily need fast action in sports. According to Jurado-Lavanant et al 9 , one should take into account the principle of specificity: although plyometric training in water appears to be safer than plyometric training on land, where performance depends on the ability to immediately perform a maximum vertical jump towards a target (DJ) or the repetition of high-intensity actions (sequential rebound jumps), better results are probably achieved through plyometric training on dry land. Nevertheless, it is believed that in situations where there is need for load control during landings, for example, in a period of preparation for plyometric training or in a process of returning to practice after a period of rehabilitation, the aquatic environment can be useful and motivating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation